Dewatering Of Sludge Produced From Metallurgical Wastewaters During Electrolyte Regeneration, Copper Refining And Precious Metals Recovery - Z. Stanojevic-Simsic (Society for Mining, Metallurgy & Exploration, 2006)
The aim of this paper was to study sludge dewatering. The sludge which was examined in laboratory scale was produced by neutralization of a mixture of metallurgical wastewaters. Experiments were carried out using synthetic wastewaters with chemical composition similar to that of metallurgical wastewaters, resulting from electrolyte regeneration, copper refining and precious metals recovery. During investigations gravitational and vacuum techniques were examined. Parameters such as water volume, height of sludge and time of dewatering were monitored. In this paper the results obtained are presented and discussed. The application of vacuum filtration enables better dewatering and compaction of sludge.